Data Sheet 1_An evolving role in the NICU: a study of the tasks, knowledge, skills, and practice demographics of the neonatal therapist.pdf - Alicia Fernandez-Fernandez (9139193) (2025)
Objectives To describe current practice and roles of the neonatal therapist. Study design A Neonatal Therapy Practice Analysis was distributed to neonatal therapists (physical therapists, occupational therapists, and speech-language pathologists) in 2019–2020 via social media, email, newsletters, and conference materials. Results There were 1,313 respondents from 1,110 different hospitals. 41.7% (n = 277) were occupational therapists, 29.3% (n = 195) were physical therapists, and 29.0% (n = 193) were speech-language pathologists. 760 (59.1%) worked in level III NICUs, while 248 (19.3%) worked in level II NICUs and 273 (21.2%) in level IV NICUs. 166 (28.1%) of respondents were Certified Neonatal Therapists (CNTs), which was related to higher number of full-time equivalent (FTE) positions per bed (β = 1.066, SE = 0.478, p = 0.026) and higher percentage of infants served in the NICU (β = −3.2, SE = 0.589, p < 0.001). We observed a median of one therapy FTE per 17 NICU beds (range of 1 FTE per 10–200 beds). Higher acuity NICU levels (β = 2.23, SE = 0.197, p < 0.001) and NICUs with higher number of beds (β = 2.497, SE = 0.285, p < 0.001) had more neonatal therapy FTEs. Survey respondents reported working with a median of 76.0% of infants in their respective NICUs (IQR 65%–90%, range 1%–100%). There was a higher percentage of infants served in higher acuity NICUs (β = 4.358, SE = 1.517, p = 0.004), in NICUs with a higher number of beds (β = 0.058, SE = 0.029, p = 0.047), when there was a productivity standard (β=11.47, SE = 1.9, p < 0.001), and where there was a higher number of neonatal therapy FTEs (β = 1.0, SE = 0.239, p < 0.001). 294 (46%) of respondents reported having standing orders, which was related to a higher percentage of infants served in the NICU (β = −1.109, SE = 0.393, p < 0.001) and to having a productivity standard (β = −0.467, SE = 0.139, p < 0.001). 65.3% (n = 415) of respondents reported having productivity standards to meet each day, with a range between 50%–80%. Conclusion This practice analysis provides insights into the changing landscape of neonatal therapy.